Zur Sommerwitterung in der Bundesrepublik Deutschland - Frankenberg, Peter (ERDKUNDE, 1984)
The analysis of the spatial and temporal patterns of the summer time weather in the FRG presents a map of the mean annual numbers of days of summer-time weather. It is evident that the 50th parallel nearly separates a region with summer temperatures above average (Southern Germany) from a region with summer temperatures below average (Northern Germany). The analysis further identifies years of maximum similarity of summer-time weather by means of a PCA (principal component analysis) - followed by an analysis of spatial patterns of these similarities in time. Two main boundaries of summer-time weather appear according to the number of days with a maximum temperature >25°C and the number of days with precipitation >0,1 mm: the Main and Nahe valleys and the northern boundary of the Rheinisches Schiefergebirge. Southwestern Germany mostly shows a marked affinity with Northern Germany.